THE PRINCIPAL'S ROLE IN IMPROVING TEACHER PERFORMANCE - Danial Missa; Catur Wahyudi; Yustina Ndung (International Journal of Business, Law and Political Science, 2026)
Objective: This study aims to analyze the role of the principal in improving teacher performance at SDN 015 Mook Manaar Bulatn, West Kutai Regency, Indonesia, based on the Regulation of the Minister of Primary and Secondary Education of the Republic of Indonesia Number 7 of 2025 concerning the Assignment of Teachers as School Principals. It also identifies the supporting and inhibiting factors affecting the implementation of the principal’s leadership role. Method: This study employed a descriptive qualitative approach. Data were collected through interviews, observations, and document analysis involving the principal, classroom teachers, and the school supervisor. Data were analyzed using the interactive model of data reduction, data display, and conclusion drawing to obtain a comprehensive understanding of the principal’s role in improving teacher performance. Results:  The findings reveal that the principal effectively implemented the seven leadership roles of educator, manager, administrator, supervisor, leader, innovator, and motivator, contributing to improved teacher performance. Leadership and motivation were rated excellent, while the remaining dimensions were rated good. Teacher performance was supported by strong leadership commitment, collaboration, and stakeholder support but constrained by limited resources, supervision time, technological competence, and reward systems. Novelty: This study contributes to the literature by examining principal leadership through the perspective of Indonesia’s newly enacted Ministerial Regulation No. 7 of 2025 and integrating it with Mulyasa’s seven-dimensional leadership framework, providing updated empirical evidence on policy-based school leadership for improving teacher performance in primary education.